2009
DOI: 10.1007/s12020-009-9236-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel indicator of widespread endothelial damage and ischemia in diabetic patients: ischemia-modified albumin

Abstract: Ischemia-modified albumin (IMA) is a novel marker of tissue ischemia. Nowadays, IMA is accepted as a marker of oxidative stress. In this study, we aimed at establishing an association between IMA and hyperglycemia, blood pressure, lipid parameters, microvascular complications, hsCRP, and microalbuminuria in type 2 diabetes patients without overt macrovascular disease and acute ischemia. Fifty type 2 diabetes mellitus patients without a history of macrovascular disease or end-stage renal disease were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 94%
“…18,19 IMA has been well accepted in the literature as a marker of OS, and its elevation has been associated with endothelial dysfunction, inflammation, and hyperglycemia in different types of diabetes with and without complications. [17][18][19][30][31][32][33][34] Hyperglycemia in DM is linked to OS, and retinal exposure to hyperglycemia activates multiple enzymes/ pathways accelerating OS and development of DR. [9][10][11]35 Hyperglycemia promotes increased IMA formation probably owing to mechanisms of hypoxia and OS. [17][18][19] Interestingly, it was reported that increased glycosylation of hemoglobin increases its affinity for oxygen, therefore, preventing its release at the tissue inducing hypoxia and OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, infants with RDS expose to severe hypoxia [4]. Current studies have determined that cord blood levels of IMA are higher in perinatal asfixia and complicated deliveries associated with fetal distress, hypoxia, and oxidative stress in newborns [11,12,19,20], and IMA has been declared to be a good marker for diagnosis of asphyxia. RDS is known a severe disease that leads to severe hypoxia and further deleterious neurodevelopmental outcomes of preterm infants and mortality without appropriate respiratory support and surfactant therapy.…”
Section: Discussionmentioning
confidence: 99%